Gone bird in the glass hours : a poem play - Asher, Zachary (Agha Shahid Ali prize in poetry., 2020)
"Zachary Asher's second collection, gone bird in the glass hours, is a play in verse, featuring seven voices. Its opening act introduces readers to a young Rabbi, bewildered and bent by personal grief, while still trying to lead his congregation. The Rabbi is guided and beguiled by another figure, the elusive Blue Postman, who shepherds the Rabbi through his journey through "the glass hours.""--